Hydrophilic gallic acid–imprinted polymers over magnetic mesoporous silica microspheres with excellent molecular recognition ability in aqueous fruit juices. (15th July 2015) - Hu, Xin; Xie, Lianwu; Guo, Junfang; Li, Hui; Jiang, Xinyu; Zhang, Yuping; Shi, Shuyun
Highlights: Hydrophilic Fe3 O4 @SiO2 @mSiO2 @MIPs with excellent recognition ability. The composites combined the advantages of Fe3 O4, mSiO2, PDA and MIPs. Fast, efficient and selective extraction of GA from fruit juice. Abstract: Hydrophilic molecularly imprinted polymers (MIPs) for gallic acid (GA) were prepared with excellent recognition ability in an aqueous solution. The proposed MIPs were designed by self-polymerization of dopamine (DA) on magnetic mesoporous silica (Fe3 O4 @SiO2 @mSiO2, MMS) using GA as template. Resulting Fe3 O4 @SiO2 @mSiO2 @MIPs (MMS–MIPs) were characterized by transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FT-IR), thermo-gravimetric analysis (TGA), Brunauer–Emmett–Teller (BET), vibrating sample magnetometer (VSM), and evaluated by adsorption isotherms/kinetics and competitive adsorption. The adsorption behavior between GA and MMS–MIPs followed Langmuir and Sips adsorption isotherms with a maximum adsorption capacity at 88.7 mg/g and pseudo-second-order reaction kinetics with fast binding (equilibrium time at 100 min). In addition, MMS–MIPs showed rapid magnetic separation (10 s) and stability (retained 95.2% after six cycles). Subsequently, MMS–MIPs were applied for the selective extraction and determination of GA from grape, apple, peach and orange juices (4.02, 3.91, 5.97, and 0.67 μg/g, respectively). Generally, the described method may pave the way towards rationally designing more advanced hydrophilic MIPs.